“Efecto de la fertilización orgánica y algas marinas en el rendimiento del maíz dulce (Zea mays L.), en la zona de Babahoyo” - Vera Vecilla, Jorge Alexander (2018)
VIII. SUMMARY The present experimental work was carried out on the grounds of the Experimental Farm "San Pablo" of the Technical University of Babahoyo, located at Km. 7.5 of the Babahoyo - Montalvo highway, with geographic coordinates 110597.97 UTM of latitude. South and 277438.26 UTM of west longitude and with altitude of 8 msnm. The super sweet BANDIT F1 sweet corn was used as planting material, the objectives were: to evaluate the effect of organic fertilization and dosage; identify the optimum dose of organic fertilizers with the respective doses for the production of the sweet corn crop and economically analyze the treatments under study. The treatments studied were Algasoil, in doses of 500 kg / ha; AlgaTec 2.0 L / ha; Algasoil + AlgaTec 400 kg / ha soil + 1.0 L / ha foliar; Algasoil + AlgaTec 600 kg / ha soil + 1.5 L / ha foliar; Algasoil + AlgaTec 800 kg / ha soil + 2.0 L / ha foliar and the conventional control with 140 kg / ha of N + 80 kg / ha of P + 90 kg / ha of K. The range of application of the products was at 8, 20 and 40 days after sowing. The experimental design "Complete block at random" BCA was used, with 6 treatments and 4 repetitions For the evaluation and comparison of means, the Tukey test was used at 95% probability. Soil preparation, sowing, weed control, irrigation, fertilization, phytosanitary control and harvesting The data evaluated were plant height and ear insertion, days to ear maturation and length, number of grains / plant, yield per hectare and economic analysis For the results obtained it was determined that the application of Agasoil and Algatec, if it reflected effects on the fertilization in the sweet corn cultivation, in the area of Babahoyo, the plant height and height of insertion of the ear obtained better averages with the use of 140 kg / ha of N + 80 kg / ha of P + 90 kg / ha of K, the use of foliar AlgaTec in a dose of 2.0 L / ha was the treatment that matured in meno r time, the average cob length was 0.19 cm; grain numbers per plant stood out with the use of Algasoil + AlgaTec in doses of 800 kg / ha soil + 2.0 L / ha foliar and the highest grain yield and economic analysis was presented with the conventional control of 140 kg / ha of N + 80 kg / ha of P + 90 kg / ha of K with net profit of $ 417.02.